Supply chain and logistics management : an integrated approach - Baisya, Rajat K. (Routledge, 2024)
"This textbook discusses supply chain management and provides comprehensive overview of all the key activities and issues of supply chain and logistics functions as an integrated discipline. Taking a comprehensive approach, it reviews end to end supply chain management from procurement to production to warehousing, distribution and customer service. It explores how each interface can be managed with an ultimate objective of providing superior customer experience to ensure satisfaction at least cost while delivering incremental value in a competitive environment. This volume guides on designing effective development and management of the supply chain network, which is an invaluable source of sustainable, competitive advantage in today's turbulent global marketplace; Examines the complexities and challenges of catering to the flexible and fluctuating customer demand, warehousing, channel distribution and transportation, global logistics value chain management, and performance management; Discusses short practical cases to explain the decision-making process with respect to manufacturing decisions and inventory for efficient working capital management, both of which are critical for supply chain performance; Explores performance management matrix, maturity models and so on. This book will be useful to the students, researchers, and faculty from the field of business management, supply chain and logistics management, mechanical and civil engineering. It will also be an invaluable companion to consultants and business executives working in the field of supply chain and logistics"-- Provided by publisher.
Keywords: Business logistics -- Management.; elektronické knihy; electronic books